The Influence of Family Environment on Students' Academic Achievement at SMAN 1 Sungai Rumbai - Dedri Yasmi; Widya Dwi Anggraini; Lesis Andre; B.R.E. Yunanda (The Future of Education Journal, 2025)
The family environment is considered one of the key factors supporting students’ academic achievement. However, the direct influence of the family environment on learning outcomes still requires further examination, particularly among students at SMAN 1 Sungai Rumbai. Therefore, this study aims to analyze the influence of the family environment on students’ academic achievement at the school. This research employed a quantitative method using a survey approach. Data were collected from 70 students as research samples using a questionnaire instrument that had been tested for validity and reliability. Data analysis was conducted using SPSS version 21 through Pearson correlation tests and simple linear regression to determine the relationship and influence of the family environment variable on academic achievement. The research findings indicate that the family environment significantly influences students' academic achievement at SMAN 1 Sungai Rumbai, with the regression equation Y = 51.240 + 0.635X. The study reveals a positive and significant effect of the family environment on students’ academic achievement, with a regression coefficient of 0.635 and a significance value of 0.000. Descriptive analysis from 70 respondents shows an average family environment score of 47.87, with data distribution tending toward higher values. The research instrument was proven valid and reliable, with a Cronbach’s Alpha value above 0.97. Pearson correlation test results indicate a very strong relationship (r = 0.853), and the coefficient of determination of 0.727 suggests that 72.7% of the variation in students' academic achievement is explained by the family environment variable, while 27.3% is explained by other variables not examined in this study.